Grant's rival: the USSR and Latin America - Blaser, Cole (University of Pittsburg Press PittsburgUS, 1987)
Examines the purposes of the USSR in its much expanded relations with Latin America, the benefits and costs of those relations, and Soviet impact on the region. Looks at the nature and political significance of Soviet trade with the area. Questions Soviet tactics and strategy in promoting national liberation movements and revolutionary change in the area, as well as its position with respect to peaceful and armed revolutionary strategies. Seeks to determine what are the major converging and diverging interests in the Soviet-Cuban relationship.